2023
DOI: 10.1111/irv.13137
|View full text |Cite
|
Sign up to set email alerts
|

State and situation of avian influenza in the Eastern Mediterranean Region

Abstract: Avian influenza viruses have had a significant burden of disease on animal and public health in countries of the Eastern Mediterranean Region. In this review, we aimed at describing the state of avian influenza in the region from 2011 to 2021. We gathered information available through the peer‐reviewed scientific literature, public gene sequence depositories, OIE World Animal Health Information System platform, World Health Organization FluNet, Joint External Evaluation reports, and governmental, Food and Agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Avian influenza A (H5N1) remains a major concern in the EMR and, according to a recent study, approximately 10,000 outbreaks due to various types of avian influenza were reported in birds and other species in the EMR from 2011 to 2021 (24). The majority of these avian outbreaks were reported in Iran, Egypt, and Iraq, whereas most other countries either reported no outbreaks or very few outbreaks in avian species.…”
Section: Avian Influenzamentioning
confidence: 99%
“…Avian influenza A (H5N1) remains a major concern in the EMR and, according to a recent study, approximately 10,000 outbreaks due to various types of avian influenza were reported in birds and other species in the EMR from 2011 to 2021 (24). The majority of these avian outbreaks were reported in Iran, Egypt, and Iraq, whereas most other countries either reported no outbreaks or very few outbreaks in avian species.…”
Section: Avian Influenzamentioning
confidence: 99%
“…HPAI H5N1 was first introduced to the EMR in Turkey in 2005 1 and into Egyptian poultry in 2006. 2 Low pathogenic avian influenza (LPAI) H9N2 virus was detected in 2011. Both viruses became endemic in the domestic poultry population.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Egypt reported the highest number of (HPAI) H5N1 human cases and reported few cases of (LPAI) H9N2. 2 In response, a research surveillance program for avian influenza viruses was established. 3 This program provided insights into the epizootic situation showing that H5N1 and H9N2 viruses were constantly evolving genetically and antigenically and that both viruses were co‐circulating and co‐infecting.…”
Section: Introductionmentioning
confidence: 99%